Analysis of the Elitism Theory from the Perspective of Political Sociology - Habibi, Mohammad Khalid (Journal of Social Sciences - Kabul University, 2024)
In political sociology, the theory of elitism is critical and is based on the principle that the nature of its elites determines the nature of every society. This article aims to understand, explain, and analyze this theory from a political sociology perspective. The significance of this research lies in the theory's potential to elucidate the nature of political structures within societies. This article employs a qualitative literature review method. The findings indicate that elitism has been a major theory in political sociology, not only in the past but also in the contemporary era. This theory is not limited to Western political thought but can also be derived from Islamic sources. Islamic scholars have provided valuable insights into the theory of elitism.